Amblyostatin-1, the first salivary cystatin with host immunomodulatory and anti-inflammatory properties from the Neotropical tick Amblyomma sculptum, vector of Brazilian spotted fever - Wilson Santos Molari; Mohamed Amine Jmel; Mohamed Amine Jmel; Josiane Betim Assis; Alan Frazão-Silva; Júlia Moura Bernardi; Gretta Huamanrayme; José María Medina; Eliane Esteves; Solange Cristina Antão; Gabriel Cerqueira Alves Costa; Aparecida Sadae Tanaka; et al. (Frontiers in Immunology)
IntroductionThe Neotropical tick Amblyomma sculptum is the primary vector of Rickettsia rickettsii, the causative agent of Brazilian spotted fever, a disease associated with high fatality rates. Tick saliva, a complex mixture of bioactive molecules essential for successful blood feeding, facilitates pathogen transmission and modulates host immune responses. A comprehensive evaluation of the salivary gland transcriptome database reveals that protease inhibitors are abundantly expressed molecules in tick saliva during feeding. Thus, this study aims to describe and characterize the most expressed member of the cystatin family identified in Amblyomma sculptum salivary transcriptome, named Amblyostatin-1. MethodsBioinformatic tools were employed for in silico analysis of the Amblyostatin-1 sequence and structure. A recombinant version of Amblyostatin-1 was expressed in an Escherichia coli system, evaluated against a panel of cysteine proteases in biochemical assays, and used to generate antibodies in immunized mice. The biological activities of Amblyostatin-1 were assessed by its effects on dendritic cell maturation in vitro and in a carrageenan-induced inflammation model in vivo.ResultsBased on its sequence and predicted three-dimensional structure, Amblyostatin-1 is classified as an I25B cystatin, and its recombinant form selectively inhibits cathepsins L, C, and S at different rates, with a low nanomolar Ki value of 0.697 ± 0.22 nM against cathepsin L. Regarding its biological activities, recombinant Amblyostatin-1 partially affects LPS-induced dendritic cell maturation by downmodulating the costimulatory molecules CD80 and CD86 at higher micromolar concentrations (3 µM) while promoting IL-10 production at nanomolar concentrations (100 nM). The apparent lack of Amblyostatin-1-specific antibody responses in immunized mice suggests an impairment of antigen processing and presentation in vivo. Furthermore, in a carrageenan-induced inflammation model, Amblyostatin-1 decreased edema formation and neutrophil infiltration into the skin without affecting other myeloid cells.DiscussionThese findings establish Amblyostatin-1 as a novel salivary cystatin with immunomodulatory and anti-inflammatory properties, highlighting its potential as an immunobiological agent.